(untitled) (Música Hodie, 2021)
The study investigates musical compositions via quantification using mathematical methods. The investigation is based on Franz Schubert’s song cycle Die Winterreise, Robert Schumann’s song cycle Myrthen, and on works by other composers. The study obtained p-value estimates for each quantity to assess its adequacy and probability of getting reliable result. The obtained p-values show probability of obtaining corresponding mean value of the investigated parameters. The results will allow finding objective criteria for describing his work in comparison with the works of other composers. They are useful for restoring musical notations, analyzing and classifying works of unknown authorship.